2020
DOI: 10.1108/ijppm-07-2019-0317
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the enablers of industry 4.0 in the Indian manufacturing industry

Abstract: PurposeThe vision of Industry 4.0 concept is to create smart factories that will change the current processes of production and manufacturing system using smart machines to produce smart and intelligent products. The main aim of this research is to explore the enablers with regard to Industry 4.0 application in manufacturing industry in India as the available literature shows that manufacturing sector is still doubtful about the implementation of Industry 4.0.Design/methodology/approachSeventeen enablers that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 61 publications
3
39
0
1
Order By: Relevance
“…Here we provide a thorough discussion of the identified actions and sub-actions, in light of the existing literature on Industry 4.0. Some identified actions confirm the messages already provided by some scholars in the literature, such as the importance to innovate by adopting the new technologies and reviewing both strategy and organizational structure (Veile et al, 2019;Cimini et al, 2020); the promotion of an innovation culture (Jain and Ajmera, 2021); the development of training activities through knowledge management programs (Kahle et al, 2020;Veile et al, 2019); and the need to develop proper (ICT) infrastructures (Moktadir et al, 2018).…”
Section: Discussionsupporting
confidence: 61%
“…Here we provide a thorough discussion of the identified actions and sub-actions, in light of the existing literature on Industry 4.0. Some identified actions confirm the messages already provided by some scholars in the literature, such as the importance to innovate by adopting the new technologies and reviewing both strategy and organizational structure (Veile et al, 2019;Cimini et al, 2020); the promotion of an innovation culture (Jain and Ajmera, 2021); the development of training activities through knowledge management programs (Kahle et al, 2020;Veile et al, 2019); and the need to develop proper (ICT) infrastructures (Moktadir et al, 2018).…”
Section: Discussionsupporting
confidence: 61%
“…, 2018), which were conducted in the manufacturing industry of western countries such as Denmark, Norway and Germany, respectively. Similarly, in the eastern context, Jain and Ajmera (2020) and Subramanian et al. (2021) did not report these factors.…”
Section: Discussionmentioning
confidence: 86%
“…(2020) suggested that improvements in government regulation and technological infrastructure could facilitate the adoption of Industry 4.0 technologies. Similarly, Jain and Ajmera (2020) showed that Internet facility, financial support and skill training were the major enablers of I4.0. Hence, facilitating factors as such may play a significant role in the decision to start the digital transformation, as they may expedite the acquisition of required resources.…”
Section: Literature Reviewmentioning
confidence: 98%
“…This analysis comes under the purview of data science. Traditional data science has been experiencing a paradigm shift due to the advent of deep learning technology (Bag & Pretorius, 2020 ; Jain & Ajmera, 2020 ), which has gained popularity for surpassing traditional machine learning (Ghobakhloo, 2018 ; LeCun et al, 2015 ). Deep learning can handle all types of structured, semi-structured, or even unstructured data, including big data.…”
Section: Theoretical Background and Development Of Conceptual Modelmentioning
confidence: 99%